2009
DOI: 10.1143/jjap.48.081201
|View full text |Cite
|
Sign up to set email alerts
|

Electronic States of P Donors in Si Nanocrystals Embedded in Amorphous SiO2Layer Studied by Electron Spin Resonance: Hydrogen Passivation Effects

Abstract: Si nanocrystals (SiNCs) embedded in formed amorphous SiO 2 layer and P nanoscale doping have been investigated by electron spin resonance (ESR) measurements at low temperatures. Hydrogen atom treatment is found to be required to determine the proper doping effects and electronic states of doped donors and quasi-conduction electrons in SiNCs. The dependences of microwave power and temperature for the ESR hyperfine structure of isolated P donors indicate that the spin-lattice relaxation time T 1 becomes longer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This method is called hydrogen passivation in general, or hydrogen atom treatment (HAT) in our case. 12,25) The permeability or mobility of H atom is much higher than that of hydrogen molecules. 10,12) The electron spin resonance (ESR) measurements were done for the prepared samples at 4.2 K with and without laser light irradiation at each wavelength of 633, 532, and 442 nm.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This method is called hydrogen passivation in general, or hydrogen atom treatment (HAT) in our case. 12,25) The permeability or mobility of H atom is much higher than that of hydrogen molecules. 10,12) The electron spin resonance (ESR) measurements were done for the prepared samples at 4.2 K with and without laser light irradiation at each wavelength of 633, 532, and 442 nm.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…7) Impurity doping is a key technology for SiNCs and SiNWs as well as for bulk Si in order to control electrical and optical properties. [8][9][10][11][12][13][14][15][16][17][18][19] Our recent study 10,12) revealed that proper hydrogen passivation is needed to obtain a better SiNCs/SiO 2 system with little interface defects and for the study of impurity doping and quasi-conduction electrons (QCE). In general, since the number of Si atoms contained in each SiNC with a diameter of 3 and 5 nm is estimated to be approximately 680 and 3100, the discrete levels in the quasiconduction band (QC-band) have a separation larger than an energy of 0.33 meV.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations